Root functioning in tropical high-elevation forests: environmental vs biological control of root water absorption - Graefe, Sophie; Leuschner, C; Coners, H; Hertel, D. (Elsevier, 2011)
Lowered temperatures may reduce the root water uptake of tropical trees at high elevations through several mechanisms; however, field studies to test their relevance are lacking. We measured sap flux density (J) in small-diameter tree roots across a 2000-m elevation transect in a tropical mountain forest for quantifying the effects of temperature (Ta), VPD and soil moisture (?) on root water flow and uptake at different elevations. Recently developed miniature heat balance-sap flow gauges were applied to roots of about 10 mm in diameter in mountain forest stands at 1050, 1890 and 3060 m a.s.l. in the Ecuadorian Andes and the measured flow was related to anatomical properties of the root xylem. Between 1050 and 3060 m, mean J decreased to about a third. VPD was the most influential environmental factor controlling J at 1050 and 1890 m, while Ta was the key determinant at 3060 m. Large vessels were absent in the root xylem of high-elevation trees which resulted in a 10-fold decrease of theoretical hydraulic conductivity (khtheor) between 1050 and 3060 m. We conclude that both physical limitations (reduced VPD, increased viscosity of water) and biological constraints (large decrease of khtheor) result in a significantly reduced J and root water uptake of the trees in high-elevation tropical forests.